A silk fiber wound repair membrane loaded with astaxanthin and its preparation method and application

By loading astaxanthin filament nanoparticles on the silk fiber trauma repair membrane, the shortcomings of traditional dressings in antioxidant, anti-inflammatory and permeable air permeability are solved, and rapid healing of the trauma surface is achieved.

CN117338988BActive Publication Date: 2025-02-25SOUTHWEST UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311485193.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-07
Publication Date
2025-02-25
Estimated Expiration
2043-11-07

AI Technical Summary

Technical Problem

Traditional trauma repair dressings do not perform well in anti-inflammatory, antioxidant and permeable water and breathability, making it difficult to promote rapid healing of the trauma surface.

Method used

Astaxanthin-loaded silk fiber trauma repair membrane is used, which treats silk fiber films by hot pressing and surface slight dissolving, and self-assembles astaxanthin silk fiber nanoparticles on its surface to enhance antioxidant and anti-inflammatory properties.

Benefits of technology

The membrane demonstrates excellent antioxidant, biocompatibility and anti-inflammatory properties, significantly promoting rapid healing of wound surfaces and addressing the shortcomings of traditional dressings in these aspects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117338988B_ABST
    Figure CN117338988B_ABST
Patent Text Reader

Abstract

The present invention provides a silk fiber wound repair membrane loaded with astaxanthin, and a preparation method and application thereof, belonging to the technical field of wound repair materials. The present invention uses a flat silk fiber film as a base material, and loads astaxanthin silk nanoparticles on the surface. The astaxanthin-loaded silk fiber wound repair membrane provided by the present invention has excellent antioxidant properties, excellent biocompatibility, anti-inflammatory properties, and the performance of promoting wound healing, and can be used to deal with different types of wound management problems such as infectious wound repair and postoperative wound repair, and effectively solves the shortcomings of traditional dressings in terms of anti-inflammatory and antioxidant properties and poor water permeability and air permeability, and avoids secondary damage to the wound surface caused by the dressing. The present invention uses a flat silk fiber film as a base material, which not only has the good biocompatibility, air permeability and water permeability, and mechanical properties of silk, but also can better control the size, and can be designed according to different needs to have a shape and size that fits the skin better.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of wound repair materials, and in particular to an astaxanthin-loaded silk fiber wound repair membrane and a preparation method and application thereof. Background Art

[0002] Skin covers the entire body and is one of the largest organs in the human body. It is also the first barrier for the human body to face the outside world. The skin contains abundant blood vessels and neural networks, and can continuously metabolize and self-repair. In daily life, the skin will inevitably be injured to varying degrees. The human body can still defend against minor skin injuries, but major skin injuries may cause metabolic disorders, immune imbalance, electrolyte imbalance, and infection caused by pathogen invasion. In severe cases, shock and death may occur. In order to prevent the above situations from happening, wound repair materials are needed to help the human body heal wounds.

[0003] However, traditional wound repair dressings (e.g., inert wound repair dressings that are mostly solid, including plaster, gauze, bandages, etc.) only cover the wound to prevent wound infection, but have no effect on promoting wound healing. They have poor anti-inflammatory, antioxidant properties and water permeability and can easily cause secondary damage to the wound surface if used improperly.

[0004] As a pure natural protein fiber, silk contains 18 essential amino acids for the human body. It has the advantages of being smooth, soft, skin-friendly, breathable, and biocompatible. It is considered to be an ideal material for preparing biomaterials and has been used in the repair of human skin, blood vessels, nerves, bones / cartilage and other tissues and organs. Studies have shown that leucine and histidine in silk components are essential amino acids for skin wound healing. Silk materials applied to wounds can be directly absorbed by the skin, promoting wound healing and inhibiting bacterial infection, especially promoting the regeneration of epidermal tissues such as burns and scalds. In addition, the natural humidity-regulating factors in the stratum corneum of the skin are composed of amino acids, pyrrolidone hydroxy acids, lactates and other substances. The silk polypeptides in silk contain soluble proteins, random coiled molecular conformations, and many polar hydrophilic groups on the polypeptide chains, which make the moisture content in the skin moderate, make the skin elastic, and make the skin surface smooth and soft.

[0005] However, pure silk does not have antioxidant properties as a wound repair material, and it is difficult to achieve the effect of promoting rapid healing of the wound surface. Summary of the invention

[0006] In view of this, the present invention aims to provide a silk fiber wound repair membrane loaded with astaxanthin and its preparation method and application. The silk fiber wound repair membrane loaded with astaxanthin provided by the present invention has excellent antioxidant, anti-inflammatory and water permeability, and can effectively promote the rapid healing of wound surfaces.

[0007] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0008] The present invention provides a method for preparing an astaxanthin-loaded silk fiber wound repair membrane, comprising the following steps:

[0009] hot-pressing the flat silk film to obtain a hot-pressed flat silk fiber film;

[0010] Placing the hot pressed flat silk fiber film in a ternary solution for surface micro-dissolution treatment to obtain a pretreated flat silk fiber film; the ternary solution comprises CaCl2, ethanol and water;

[0011] Dissolving freeze-dried silk fibroin in water to form a silk fibroin solution, adding astaxanthin to obtain a mixed solution of astaxanthin and silk fibroin, and then dropping the mixed solution into an acetone solution to obtain astaxanthin-loaded silk fibroin nanoparticles;

[0012] The pretreated flat silk fiber film is immersed in an astaxanthin fibroin nanoparticle solution and oscillated to mix, so that the astaxanthin fibroin nanoparticles and the fiber film are self-assembled to obtain an astaxanthin-loaded silk fiber wound repair film.

[0013] Preferably, the thickness of the flat silk film is 0.05 to 0.5 mm;

[0014] The temperature of the hot pressing is 60-100° C., the pressure is 10-20 MPa, and the heat preservation and pressure holding time is 3-10 minutes.

[0015] Preferably, before the hot pressing, the flat silk film is also immersed in water.

[0016] Preferably, in the ternary solution, the molar ratio of CaCl2, ethanol and water is 0.9-1:2:6.5-8.

[0017] Preferably, the surface micro-dissolution treatment is performed at a temperature of 55 to 75° C. and for a time of 5 to 30 minutes.

[0018] Preferably, the mass ratio of astaxanthin to silk fibroin is 0.1-0.2:1.

[0019] Preferably, the particle size of the astaxanthin silk fibroin nanoparticles is 150 to 250 nm.

[0020] Preferably, the concentration of the astaxanthin silk fibroin nanoparticle solution is 2 to 6 mg / mL;

[0021] The load time is 4 to 36 hours.

[0022] The present invention provides an astaxanthin-loaded silk fiber wound repair membrane prepared by the above-mentioned preparation method, comprising a flat silk fiber film and astaxanthin silk nanoparticles loaded on the surface of the flat silk fiber film.

[0023] The present invention provides application of the above-mentioned astaxanthin-loaded silk fiber wound repair membrane in the preparation of medical dressing consumables.

[0024] The invention provides a method for preparing a silk fiber wound repair membrane loaded with astaxanthin, comprising the following steps: hot-pressing a flat silk film to obtain a hot-pressed flat silk fiber film; immersing the hot-pressed flat silk fiber film in a ternary solution for surface treatment to obtain a pretreated flat silk fiber film; the ternary solution comprises CaCl2, ethanol and water; dissolving freeze-dried silk fibroin in water to form a fibroin solution, adding astaxanthin to obtain a mixed solution of astaxanthin and fibroin, and then dropping the mixed solution into an acetone solution to obtain astaxanthin-loaded silk fibroin nanoparticles (ASTA-SFNPs for short); immersing the pretreated flat silk fiber film in an astaxanthin-silk fibroin nanoparticle solution for oscillation mixing to allow the astaxanthin-silk fibroin nanoparticles to self-assemble with the fiber film to obtain the astaxanthin-loaded silk fiber wound repair membrane. The present invention uses a flat silk fiber film as a base material, which not only has the good biocompatibility, air permeability, water permeability, and mechanical properties of silk, but also can better control the size and can be designed into a shape and size that better fits the skin according to different needs.

[0025] In the present invention, astaxanthin, as an efficient pure natural antioxidant, has a special molecular structure, can pass through the outer wall of human cells, directly remove oxygen free radicals in cells, enhance cell regeneration ability, maintain human functional balance and reduce the accumulation of aging cells; silk fibroin has good biocompatibility, low immunogenicity, processability, degradability, and the degradation products are non-toxic and harmless, and have good healing ability. This application uses a flat silk fiber film as a base material, and the surface is loaded with astaxanthin silk fibroin nanoparticles. The resulting astaxanthin-loaded silk fiber wound repair film has excellent antioxidant properties, excellent biocompatibility, anti-inflammatory properties and wound healing performance, which can be used to treat different types of wound management problems such as infectious wound repair and postoperative wound repair, effectively solving the shortcomings of traditional dressings in terms of anti-inflammatory and antioxidant properties and poor water permeability and air permeability, and avoiding secondary damage to the wound surface caused by the dressing. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is a scanning electron microscope image of the pretreated flat silk fiber film;

[0027] Figure 2 is the contact angle of the pretreated flat silk fiber film;

[0028] Figure 3 is the particle size distribution diagram of ASTA-SFNPs;

[0029] Figure 4 Transmission electron microscopy image of ASTA-SFNPs;

[0030] Figure 5 is the potential diagram of ASTA-SFNPs;

[0031] Figure 6 Fourier infrared spectra of SFNPs, ASTA, and 20% ASTA-SFNPs;

[0032] Figure 7 The astaxanthin nanoparticle loading rate of the astaxanthin-loaded silk fiber wound repair membrane obtained in Examples 1 to 3;

[0033] Figure 8 is the astaxanthin nanoparticle encapsulation efficiency of the astaxanthin-loaded silk fiber wound repair membrane obtained in Examples 1 to 3;

[0034] Fig. 9 Results of fluorescence analysis of cell staining experiments;

[0035] Fig.10 The wound photos of animal experiments at 0d, 3d, 7d and 14d after surgery are shown;

[0036] Fig.11 is the curve of wound contraction rate changing with time;

[0037] Fig.12 Schematic diagram of the wound healing effect of commercial dressings and PFSC-C-A6 in treating wounds. DETAILED DESCRIPTION

[0038] The present invention provides a method for preparing an astaxanthin-loaded silk fiber wound repair membrane, comprising the following steps:

[0039] hot-pressing the flat silk film to obtain a hot-pressed flat silk fiber film;

[0040] Placing the hot pressed flat silk fiber film in a ternary solution for surface micro-dissolution treatment to obtain a pretreated flat silk fiber film; the ternary solution comprises CaCl2, ethanol and water;

[0041] Dissolving freeze-dried silk fibroin in water to form a silk fibroin solution, adding astaxanthin to obtain a mixed solution of astaxanthin and silk fibroin, and then dropping the mixed solution into an acetone solution to obtain astaxanthin-loaded silk fibroin nanoparticles;

[0042] The pretreated flat silk fiber film is immersed in an astaxanthin fibroin nanoparticle solution and oscillated to mix, so that the astaxanthin fibroin nanoparticles and the fiber film are self-assembled to obtain an astaxanthin-loaded silk fiber wound repair film.

[0043] The present invention heat-presses the flat silk film to obtain a hot-pressed flat silk fiber film. In the present invention, the flat silk is preferably the flat silk obtained by five-instar mature silkworms spinning on a two-dimensional spinning bed.

[0044] In the present invention, the flat silk film is preferably obtained by layering the flat silk. In the present invention, the thickness of the flat silk film is preferably 0.05 to 0.5 mm, more preferably 0.1 to 0.4 mm, and further preferably 0.2 to 0.3 mm. In the present invention, the mass of the flat silk film is preferably 0.02 to 0.05 g, more preferably 0.03 to 0.04 g, and the shape is preferably rectangular.

[0045] In the present invention, the flat silk not only has the good biocompatibility, air permeability, water permeability, and mechanical properties of silk, but also can better control the size, and can be designed to be more suitable for the skin according to different needs. The present invention uses flat silk as the base material of the wound repair membrane dressing. Compared with traditional medical dressings and other non-silk-based medical materials, the flat silk has a unique cocoon layer structure, which well meets the requirements of water retention and air permeability in wound repair. Silk, as a natural high molecular protein, has excellent biocompatibility, healing ability, and degradability.

[0046] The present invention preferably uses a hot press to perform the hot pressing. In the present invention, the hot pressing temperature is preferably 60-100°C, more preferably 70-90°C; the pressure is preferably 10-20MPa, more preferably 15MPa; the heat preservation and pressure holding time is preferably 3-10min, more preferably 5-8min.

[0047] In the present invention, before the hot pressing, the present invention further comprises soaking the flat silk film in water. In the present invention, the soaking time is preferably 10 minutes. In the present invention, the soaking serves to make the flat silk film more compact.

[0048] The present invention places the hot-pressed flat silk fiber film in a ternary solution and performs surface micro-dissolution treatment to obtain a pretreated flat silk fiber film; the ternary solution includes CaCl2, ethanol and water; in the ternary solution, the molar ratio of CaCl2, ethanol and water is preferably 0.9-1:2:6.5-8, and more preferably 1:2:8.

[0049] In the present invention, the surface micro-dissolution treatment is preferably carried out under water bath heating conditions. In the present invention, the temperature of the surface micro-dissolution treatment is preferably 55-75°C, more preferably 60-70°C; the time is 5-30 minutes, more preferably 10-20 minutes. The present invention increases the surface roughness of the hot-pressed flat silk fiber film by treating the material surface with a ternary solution.

[0050] After the surface treatment, the present invention preferably washes and dries the obtained pretreated flat silk fiber film. In the present invention, the washing is preferably pure water washing, and the number of washings is preferably 3 times. In the present invention, the drying is preferably vacuum drying.

[0051] The invention dissolves freeze-dried silk fibroin in water to form a silk fibroin solution, adds astaxanthin to obtain a mixed solution of astaxanthin and silk fibroin, and then drips the mixed solution into an acetone solution to obtain silk fibroin nanoparticles loaded with astaxanthin.

[0052] In the present invention, the method for preparing the silk fibroin preferably comprises the following steps:

[0053] The silk cocoon shells are dissolved, boiled, filtered, centrifuged and dialyzed in sequence to obtain silk fibroin.

[0054] In the present invention, the solvent used for dissolution is preferably 0.5% sodium carbonate solution; the boiling time is preferably 30 min; the centrifugal speed is preferably 10000 rpm; and the molecular weight cutoff of dialysis is preferably 8-14 kDa.

[0055] In the present invention, the mass ratio of astaxanthin to silk fibroin is preferably 0.1-0.2:1, more preferably 0.15:1, and the mass ratio of silk fibroin to solvent is preferably 1:100.

[0056] In the present invention, the mixing method is preferably to stir and mix using a magnetic stirrer. In the present invention, the mixing time is preferably 5 hours.

[0057] After obtaining the astaxanthin-loaded silk fibroin nanoparticles, the present invention also preferably freezes and freeze-dries the obtained astaxanthin-loaded silk fibroin nanoparticles. In the present invention, the freezing is preferably performed in a -80°C refrigerator, and the freezing time is preferably 4 to 8 hours. The present invention preferably performs the freeze drying in a freeze dryer.

[0058] In the present invention, the particle size of the astaxanthin silk fibroin nanoparticles is preferably 150-250 nm, more preferably 200 nm.

[0059] In the present invention, the pretreated flat silk fiber film is immersed in an astaxanthin fibroin nanoparticle solution, and oscillated and mixed to allow the astaxanthin fibroin nanoparticles and the fiber film to self-assemble, thereby obtaining an astaxanthin-loaded silk fiber wound repair film. In the present invention, the concentration of the astaxanthin fibroin nanoparticle solution is 2 to 6 mg / mL, more preferably 3 to 5 mg / mL.

[0060] In the present invention, the oscillation mixing rate is preferably 50 rpm. In the present invention, the self-assembly temperature is preferably room temperature, and the self-assembly time is preferably 4 to 36 hours, more preferably 10 to 30 hours.

[0061] After the loading, the present invention preferably air-dries the obtained astaxanthin-loaded silk fiber wound repair membrane.

[0062] The present invention provides an astaxanthin-loaded silk fiber wound repair membrane prepared by the above-mentioned preparation method, comprising a flat silk fiber film and astaxanthin silk nanoparticles loaded on the surface of the flat silk fiber film.

[0063] In the present invention, in the astaxanthin-loaded silk fiber wound repair membrane, the loading amount of the astaxanthin silk fibroin nanoparticles is preferably 10-15 wt %.

[0064] The present invention provides application of the above-mentioned astaxanthin-loaded silk fiber wound repair membrane in the preparation of medical dressing consumables.

[0065] The astaxanthin-loaded silk fiber wound repair membrane provided by the present invention has excellent antioxidant properties, excellent biocompatibility, anti-inflammatory properties and the ability to promote wound healing, and can be used to deal with different types of wound management problems such as infectious wound repair and postoperative wound repair, and effectively solves the shortcomings of traditional dressings in terms of anti-inflammatory and antioxidant properties and poor water permeability and air permeability, thereby avoiding secondary damage to the wound surface caused by the dressing.

[0066] The astaxanthin-loaded silk fiber wound repair membrane provided by the present invention, its preparation method and application are described in detail below in conjunction with the examples, but they should not be construed as limiting the scope of protection of the present invention.

[0067] Example 1

[0068] (1) Fifty mature silkworms of the fifth age were selected and evenly placed on a silk-spinning plate. After 2 to 3 days, the mature silkworms on the plate were cleaned and the silk on the plate was peeled off from the silk-spinning plate.

[0069] Take a 5cm*5cm flat cocoon sample of Bombyx mori, soak it in water and put it into a hot press for thermoplastic molding. The temperature, pressure and time of the hot press are set at 100℃, 15MPa and 5min respectively. After hot pressing, treat it with a ternary solution (CaCl2, ethanol and water in a molar ratio of 1:2:8) at 55℃ for 10min to slightly dissolve the surface of the flat silk and obtain a pretreated flat silk fiber film.

[0070] (2) Preparation of astaxanthin silk nanoparticles

[0071] Take clean silkworm cocoon shells, dissolve and boil, filter, centrifuge, and dialyze to obtain silk fibroin. Take 50 mL of acetone in a beaker, add 10, 15, and 20 mg of astaxanthin (ASTA) and 10 mL of the 10 mg / mL silk fibroin solution prepared in the above steps, respectively, to prepare 10%, 15%, and 20% astaxanthin silk fibroin nanoparticles (ASTA-SFNPs); at the same time, prepare silk fibroin blank nanoparticles (SFNPs) without astaxanthin.

[0072] After ultrasonic treatment for 3 minutes, the ASTA-SFNPs and SFNPs of various concentrations prepared in the above steps were placed in a refrigerator at minus 80°C for freezing. After being frozen for 6 hours, they were quickly placed in a freeze dryer for freeze drying.

[0073] (3) Preparation of astaxanthin-loaded silk mask

[0074] A 5 cm × 5 cm pretreated flat silk fiber film was immersed in a 2 mg / mL astaxanthin nanoparticle solution for 36 h to obtain an astaxanthin-loaded silk fiber wound repair membrane, which was designated as PFSC-C-A2.

[0075] Example 2

[0076] Compared with Example 1, the difference is that the silk fiber wound repair membrane loaded with astaxanthin is obtained by immersing in a 4 mg / mL astaxanthin nanoparticle solution for 36 hours, and the membrane is marked as PFSC-C-A4.

[0077] Example 3

[0078] Compared with Example 1, the difference is that the silk fiber wound repair membrane loaded with astaxanthin is obtained by immersing in a 6 mg / mL astaxanthin nanoparticle solution for 36 hours, and the membrane is marked as PFSC-C-A6.

[0079] The processing conditions of different embodiments are shown in Table 1.

[0080] Table 1 Processing conditions of different embodiments

[0081]

[0082] Comparative Example 1

[0083] A pretreated flat silk fiber film without astaxanthin silk fibroin nanoparticles was used as comparative example 1.

[0084] Structural characterization

[0085] Scanning electron microscopy image of astaxanthin-loaded silk fiber wound repair membrane Figure 1 As shown, Figure 1 middle, Figure 1 In the table, 1 to 15 are PFSC-55-5 (the "55" in PFSC-55-5 means that the temperature of the surface micro-dissolution treatment is 55°C, and the "5" means that the time is 5 minutes); PFSC-55-10; PFSC-55-15; PFSC-55-20; PFSC-55-30; PFSC-60-10; PFSC-60-15; PFSC-60-20; PFSC-60-30; PFSC-65-5; PFSC-65-15; PFSC-65-20; PFSC-70-5; PFSC-70-10; PFSC-75-5. Figure 1 It can be seen that the treatment effect of the flat silk treated with ternary solution at 55°C for 10 min is the best.

[0086] The contact angle of astaxanthin-loaded silk fiber wound repair membrane is as follows Figure 2 As shown. Figure 2 It can be seen that the contact angle effect of the flat wire treated with ternary solution at 55℃ for 10min is the best.

[0087] The particle size distribution of astaxanthin silk nanoparticles is shown in Figure 3 shown. Figure 3 Among them, 1 to 4 are SFNPs; 10% ASTA-SFNPs; 15% ASTA-SFNPs; 20% ASTA-SFNPs. Figure 3 It can be seen that ASTA-SFNPs were successfully prepared by acetone volatilization method, and the particle size was concentrated around 200 nm.

[0088] Transmission electron microscopy images of astaxanthin silk nanoparticles Figure 4 shown. Figure 4 From left to right in the figure are ASTA, SFNPs, and 20% ASTA-SFNPs. Figure 4 It can be seen that the silk fibroin nanoparticles and the silk fibroin nanoparticles loaded with astaxanthin present spherical particles with smooth surface and uniform size. No blocky crystals of astaxanthin appear in the drug-loaded silk fibroin, indicating that astaxanthin is well encapsulated in the silk fibroin.

[0089] The potential diagram of astaxanthin silk nanoparticles is shown in Figure 5 As shown. Figure 5 It can be seen that the Zeta potential of astaxanthin silk nanoparticles prepared with an astaxanthin concentration of 2 mg / mL is -29.942±0.756 mV, and the absolute value is greater than 20 mV, indicating that the silk protein nanoparticle dispersion system prepared with astaxanthin at this concentration is relatively stable.

[0090] Fourier infrared spectra of SFNPs, ASTA, and 20% ASTA-SFNPs Figure 6 As shown. Figure 6 It can be seen that all the absorption peaks of silk nanoparticles can be found in astaxanthin-loaded silk protein nanoparticles. By comparing the spectra of astaxanthin and astaxanthin-loaded silk protein nanoparticles, it is found that the specific absorption peak of astaxanthin appears in astaxanthin-loaded silk nanoparticles, and the position of the characteristic absorption peak does not change. This shows that astaxanthin is successfully encapsulated in silk nanoparticles, and silk protein does not change the pharmacological properties of astaxanthin.

[0091] The astaxanthin nanoparticle loading rate of the astaxanthin-loaded silk fiber wound repair membrane obtained in Examples 1 to 3 is as follows: Figure 7 As shown, the encapsulation efficiency is Figure 8 As shown. Figure 7 , 8 It can be seen that the astaxanthin silk nanoparticles prepared when the astaxanthin concentration was 2 mg / mL had the highest drug loading capacity and encapsulation efficiency, indicating that the astaxanthin silk nanoparticles prepared under this concentration condition had a better encapsulation effect.

[0092] Test Example 1 Cell staining experiment

[0093] Experimental steps: 1. Prepare Matrigel (artificial basement membrane gel) into 0.04 μg / μL artificial basement membrane gel using serum-free culture medium RPMI-1640 for use, spread 2 μg Matrigel in each well of a 96-well plate, and place in a clean bench to air-dry overnight.

[0094] 2. Add an appropriate amount of serum-free RPMI-1640 cell culture medium (or PBS or saline) to the 96-well plate and leave it for 60 to 90 minutes.

[0095] 3. After washing away the excess gel, take the cultured tumor cancer cells at 1×10 4 The cells were inoculated in 96-well plates coated with gelatin, with 3 replicate wells, and cultured in a 37°C 5% CO2 incubator for 24 h.

[0096] 4. Add PFSC-C, PFSC-C-A2, PFSC-C-A4, and PFSC-C-A6 respectively and culture for 48 hours.

[0097] 5. Prepare the staining agent with a ratio of 2 mL PBS solution + 4 μL C-AM + 6 μL PI, and prepare the Live / Dead working solution in a light-proof condition.

[0098] 6. PBS solution washing: remove the culture medium from the 96-well plate and wash it twice with PBS solution.

[0099] 7. Cell staining: Add stain, 300 μL per well of a 96-well plate, incubate at 37°C for 20 min, wash off excess stain with PBS, and add an appropriate amount of culture medium.

[0100] 8. Fluorescence analysis: The results are detected using a fluorescence microscope. The maximum excitation of the dye-DNA complex is 490nm.

[0101] The results of fluorescence analysis of cell staining experiments are shown in Fig. 9 As shown. Fig. 9 It can be seen that PFSC-C-A4 has the most live cells and the least dead cells, indicating that PFSC-C-A4 has the least cytotoxicity.

[0102] Test Example 2 Animal Experiment

[0103] Experimental procedures: After depilation for 1 day, mice were anesthetized with ether. After the mice were completely anesthetized, they were fixed on the mouse board with their limbs in a prone position. After shaving the back of the animal, depilatory cream was applied, and it was left for 2 to 3 minutes before scraping. The residual depilatory cream was wiped off with warm water, and the residual moisture on the skin surface was wiped off with soft absorbent paper. A sterile skin trephine (Φ16mm) was pressed vertically on the skin and rotated with appropriate force until it penetrated the full layer of the skin. The skin was cut with surgical scissors to form a wound. The rat full-thickness skin wound model was used to evaluate the effect of silk nanofiber membrane dressings before and after astaxanthin nanoparticle modification on wound healing. A total of 5 groups were set up in the animal experiment, namely, silk nanofiber group (PSFC-C), silk nanofiber groups with different astaxanthin concentrations (PSFC-C-A2, PFSC-C-A6), commercial dressing control group (3M) and gauze blank group. After the operation, two mice with the same treatment were kept in each cage, and the wound infection, mouse status, wound healing, and skin lesions of the mice were observed on days 3, 7, and 14. Three mice in each group were killed on days 7 and 14 for pathological section examination.

[0104] Animal experiment results Fig.10 , Fig.11 and Fig.12 shown. Fig.10 The wound photos of each group at 0d, 3d, 7d and 14d after surgery are shown. Fig.11 is the curve of wound contraction rate changing with time, Fig.12 Schematic diagram of the wound healing effect of commercial dressings and PFSC-C-A6 in treating wounds.

[0105] On the 3rd day after surgery, in the astaxanthin silk nanofiber group, the wound surface was still covered with dressing, and the wound area was reduced to a certain extent compared with the other two groups; on the 7th day after surgery, the wound began to heal from the edge to the center, and scabs appeared. The astaxanthin silk nanofiber membrane group had the smallest wound area; on the 14th day after surgery, the scabs in each group had fallen off, and the wound center area was further reduced. The wound edge of the astaxanthin silk nanofiber membrane group was greatly reduced, and the surface was the smoothest, close to intact skin. It can be seen that at each observation time point after surgery, the PFSC-C-A2 and PFSC-C-A6 groups showed better wound contraction trends than the commercial dressing group ( Fig.10 , Fig.11 On the third day, the wound area of ​​both groups was reduced, but the wound area of ​​the experimental group was reduced more significantly, reaching a shrinkage rate of 31%. Fig.12 This is a schematic diagram of the wound healing effects of the two groups of treated wounds. This diagram intuitively shows that the healing effect of the experimental group material is better than that of the commercial dressing group.

[0106] It can be seen that astaxanthin silk nanofiber membrane dressing can promote wound healing, and the repair effect is better than commercial dressings.

[0107] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a silk fiber wound repair membrane loaded with astaxanthin, comprising the following steps: hot-pressing the flat silk film to obtain a hot-pressed flat silk fiber film; placing the hot pressed flat silk fiber film in a ternary solution to perform a surface micro-dissolution treatment to obtain a pretreated flat silk fiber film; The ternary solution includes CaCl2, ethanol and water; The freeze-dried silk fibroin is dissolved in water to form a silk fibroin solution, astaxanthin is added to obtain a mixed solution of astaxanthin and silk fibroin, and the mixed solution is then added dropwise to an acetone solution to obtain astaxanthin-loaded silk fibroin nanoparticles; the mass ratio of astaxanthin to silk fibroin is 0.1-0.2:1; and the particle size of the astaxanthin silk fibroin nanoparticles is 150-250 nm; The pretreated flat silk fiber film is immersed in an astaxanthin fibroin nanoparticle solution, and the solution is shaken and mixed to allow the astaxanthin fibroin nanoparticles and the fiber film to self-assemble, thereby obtaining an astaxanthin-loaded silk fiber wound repair film; The concentration of the astaxanthin silk fibroin nanoparticle solution is 2 to 6 mg / mL; The self-assembly time is 4 to 36 hours.

2. The preparation method according to claim 1, characterized in that: The thickness of the flat silk film is 0.05 to 0.5 mm; The temperature of the hot pressing is 60-100° C., the pressure is 10-20 MPa, and the heat preservation and pressure holding time is 3-10 minutes.

3. The preparation method according to claim 1, characterized in that: Before the hot pressing, the flat silk film is also immersed in water.

4. The preparation method according to claim 1, characterized in that: In the ternary solution, the molar ratio of CaCl2, ethanol and water is 0.9-1:2:6.5-8.

5. The preparation method according to claim 1 or 4, characterized in that: The temperature of the surface micro-dissolution treatment is 55-75° C. and the time is 5-30 minutes.

6. The astaxanthin-loaded silk fiber wound repair membrane prepared by the preparation method according to any one of claims 1 to 5 comprises a flat silk fiber film and astaxanthin silk nanoparticles loaded on the surface of the flat silk fiber film.

7. Use of the astaxanthin-loaded silk fiber wound repair membrane according to claim 6 in the preparation of medical dressing consumables.

Citation Information

Patent Citations

  • Preparation method of fibroin microsphere

    CN103341175A

  • Flat silk antibacterial composite material and preparation method thereof

    CN114032691A